Structural-Syntactic Organization of Thematic and Techniques of Composition: Aspects of Interaction - Tikhomirova, Ala (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. The study of thematic in modern musical composition as the most important element of form creation seems relevant and in demand for modern musicology. In the existing scientific works, only certain issues of its research are mentioned (V. and Yu. Kholopov, V. Valkova, N. Ryzhkova, T. Kyuregyan, V. Zaderatsky, G. Grigorieva, E. Ershova, S. Goncharenko etc.), however, there is no special work devoted to this problem. Among the important and topical issues, many remain debatable today. Some of them concern terminology, the use of the concept of “thematiс” in relation to a completely new musical language, others — the multidimensional nature of the study of musical thematiс in terms of semantics, syntax of form in terms of various composition techniques. The study of the thematic organization on the example of the works of modern Belarusian composers makes it possible to include the cultural and stylistic processes taking place in Belarusian music today in the context of the most important trends of Modern music. The scientific novelty of the study consists in: 1) a systematic approach to the concept of thematic as a category of writing in relation to modern musical composition; 2) consideration of the principles of interaction of macro- and micro-thematic; 3) analytical study of the works of the Belarusian composer E. Gutina in the chosen perspective of analysis. The purpose of the research is to consider certain aspects of the interaction of musical thematic and composition techniques in two main types of structural and syntactic organization: macrothematic and microthematic. The research methodology is based on the interaction of general scientific methods (system method, deduction method, etc.) with methods developed in theoretical musicology. We are talking, first of all, about the method of functional analysis in relation to musical thematic and musical syntax. Also significant for this study are the musical-theoretical works devoted to the problems of the author's style, form and techniques of composition in modern music, as well as the theoretical works of the composers themselves on the problems of compositional technique. The practical significance of the research can be reflected in the use of this research in university courses of musical and theoretical orientation related to the study of modern music. Conclusions and prospects for further research. The interaction of micro- and macrothematic manifests itself in different ways in various types of composition, an example of which is the compositions of the Belarusian composer E. Gutina “Wind Music” (sonorous composition) and “Majolica” (minimalist composition). At the same time, the interaction of two seemingly opposite large-scale structural and syntactic principles of the organization of thematic reveals their close relationship in the conditions of various composition techniques, both in the aspect of shaping and in the aspect of the specifics of musical perception. Further developments of the stated topic seem promising in the following areas: the study of the “composer's word”, the compilation of a glossary of terms and concepts, regarding the techniques of composition and thematic, a scientific and research look at the given problem in the mirror of the manifestation of various stylistic trends in modern music.